Centro de acolhimento para cães e gatos em situação de rua na cidade de Manaus - Figueiredo, Letícia Labanca de (Brasil, 2024)
The World Health Organization estimates that in Brazil there are more than 30 million abandoned animals, including 10 million cats and 20 million dogs. In the city of Manaus, the mark of 400.000 abandonments was exceeded in 2021. This not only increases accidents and run overs, but also spreads contagious diseases that can be a risk to the population and affecting public health as well. Despite all this problematization, there is still not enough effort put into sheltering and rehabilitating these animals in vulnerable conditions. For this reason, it is of great importance to disseminate information and promote discussions to raise awareness among the population about this urgent yet overlooked issue. Under the practical plan, the proposal is to establish a Shelter for Stray Dogs and Cats in the City of Manaus, a place that will provide shelter, care, prepare the animals for resocialization, and promote a new ideal home for them. The responsibility for all stages, from rescue to adoption, is carried out in collaboration with the assistance of existing organizations, such as the Specialized Police Department for Crimes against the Environment and Urbanism, of the State Public Security Secretariat of Amazonas, in partnership with local NGOs.